2015
DOI: 10.1080/00103624.2015.1033538
|View full text |Cite
|
Sign up to set email alerts
|

Increase in the Capacity of Interlayer Sites in a Paddy Soil as a Possible Factor Affecting the Dynamics of Fixed Ammonium at the Initial Stage of Anaerobic Incubation

Abstract: To evaluate whether the capacity of interlayer sites affects the dynamics of fixed ammonium (NH 4 + ) in a paddy soil, a combination of potassium (K)-saturation treatment and stepwise extraction of nonexchangeable K with 0.01 mol L −1 hydrochloric acid was applied to a soil incubated anaerobically up to 70 days. The capacity of interlayer sites increased with an increase of weakly fixed NH 4 + during the initial 28 days (r = 0.78, P < 0.01), and remained stable thereafter. On the other hand, the concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The ratio was, on average, 1.6-fold larger for flooded soils than unsaturated soils, indicating that the sorption and aging of RCs during 28 d since spiking were significantly (P < 0.05) more enhanced in flooded soils than in unsaturated soils. Experiments by Zhang and Scherer (2002) and Matsuoka and Moritsuka (2015) indicated that soil flooding treatments may enhance the fixation of NH4 + . This NH4 + fixation has been attributed to reductive dissolution of Fe(III) minerals, which are coating clay minerals, by anoxic microbial activity (Zhang and Scherer 2002) and to negative charge induced by the reduction of octahedral Fe(III) to Fe(II) in soil clay minerals (Nieder et al 2011).…”
Section: Differences In Rcs Mobility Between Flooded and Unsaturated Soils Due To Soil Chemical Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio was, on average, 1.6-fold larger for flooded soils than unsaturated soils, indicating that the sorption and aging of RCs during 28 d since spiking were significantly (P < 0.05) more enhanced in flooded soils than in unsaturated soils. Experiments by Zhang and Scherer (2002) and Matsuoka and Moritsuka (2015) indicated that soil flooding treatments may enhance the fixation of NH4 + . This NH4 + fixation has been attributed to reductive dissolution of Fe(III) minerals, which are coating clay minerals, by anoxic microbial activity (Zhang and Scherer 2002) and to negative charge induced by the reduction of octahedral Fe(III) to Fe(II) in soil clay minerals (Nieder et al 2011).…”
Section: Differences In Rcs Mobility Between Flooded and Unsaturated Soils Due To Soil Chemical Factorsmentioning
confidence: 99%
“…Finally, we may consider the potential long-term effects of soil flooding on the TF. The gradual fixation (Sawhney 1972) or aging of RCs in soil interlayer sites might be affected by soil flooding because of differences in soil solution K and NH4 + concentrations (Wauters et al 1996b) and of the increase in the frayed edge sites due to the reductive dissolution of Fe(III) coating on the clay minerals (Zhang and Scherer 2002;Matsuoka and Moritsuka 2015).…”
Section: Introductionmentioning
confidence: 99%